2012
DOI: 10.1179/2045772312y.0000000016
|View full text |Cite
|
Sign up to set email alerts
|

Potentially modifiable risk factors among veterans with spinal cord injury hospitalized for severe pressure ulcers: a descriptive study

Abstract: http://clinicaltrials.gov/ct2/show/NCT00105859.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 25 publications
9
29
0
Order By: Relevance
“…A general trend of development of pressure sore among people with low income was found in this study which was also common in the other reports [4,11,18,19]. Most of the respondents of this study had paraplegia (56.5%) and the principle cause was trauma which was similar to the report Rahman et al but Guihan et al reported most of their patients (73.3%) had complete spinal cord injury [10, 14,20] but in all the reports the major cause of injury was reported to be trauma whether road traffic accident or fall from height or any other mechanism of traumatic injury [4,10,11,14,20,21] ( Figure 1). Regarding the location, the authors found Buttock to be the predominant site for developing site pressure sore as evident form 67.5% patient had sore over their buttock followed by Ischial tuberosity (7.5%) and this finding was similar to Hossain et al and Ulrich et al reported the lower back to the commonest site for pressure sore [17,22] (Table 3).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A general trend of development of pressure sore among people with low income was found in this study which was also common in the other reports [4,11,18,19]. Most of the respondents of this study had paraplegia (56.5%) and the principle cause was trauma which was similar to the report Rahman et al but Guihan et al reported most of their patients (73.3%) had complete spinal cord injury [10, 14,20] but in all the reports the major cause of injury was reported to be trauma whether road traffic accident or fall from height or any other mechanism of traumatic injury [4,10,11,14,20,21] ( Figure 1). Regarding the location, the authors found Buttock to be the predominant site for developing site pressure sore as evident form 67.5% patient had sore over their buttock followed by Ischial tuberosity (7.5%) and this finding was similar to Hossain et al and Ulrich et al reported the lower back to the commonest site for pressure sore [17,22] (Table 3).…”
Section: Discussionsupporting
confidence: 87%
“…Regarding the location, the authors found Buttock to be the predominant site for developing site pressure sore as evident form 67.5% patient had sore over their buttock followed by Ischial tuberosity (7.5%) and this finding was similar to Hossain et al and Ulrich et al reported the lower back to the commonest site for pressure sore [17,22] (Table 3). In this article 44.6% of the respondents had urinary complication and 16.9% had dysuria and 10.8% had urinary incontinence which is almost similar to the report of Thiyagarajan et al and Guihan et al [16,20] (Table 3). 30 patients with pressure sore had other skin disease which may be supported by the report of Guihan and Bombardier, where 96.2% patient had associated skin disease, but Endocrine conditions like Diabetes had a significant association whit development of pressure sore along with vascular conditions which were not evident in the current study [20].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Specifically, individuals with a cervical injury reported significantly lower levels of depression than those individuals with thoracic level injuries. This is consistent with other findings in the literature 10,11,30 that may appear counterintuitive as clinicians often make the assumption that individuals with a higher level injury, and subsequently less function, will experience increased depression as compared to individuals who have retained more function. As clinicians try to identify which patients may be a risk for depression and poor outcomes postinjury, it is critical not to use level of injury or functional ability to assume degree of depression.…”
supporting
confidence: 88%
“…The evolution of ischial tuberosity PrUs is often dramatic: in a study in veterans with chronic SCI hospitalized for PrUs, pelvic PrUs (including ischial tuberosity) were most frequently categorized as stage IV in 73% of cases, 34% of these ulcers were infected, and 40% had undermining of adjacent tissue. 5 In those cases, surgical reconstruction becomes the only available option. Different types of muscular flaps with varying degrees of vascularization and tissue layers can be chosen to match the type of wound and the defect type.…”
Section: Introductionmentioning
confidence: 99%